Green Finance in Environmental Monitoring: A Bibliometric Review of Investment Trends and Policy Impact - Judijanto, Loso (Westscience Press, 2025)
The current study undertakes a bibliometric examination to analyze the emerging intersection of green finance and environmental monitoring, two critical areas that are driving the global agenda for sustainability. Based on evidence from the Scopus database and visualization using VOSviewer, the study investigates 20 years of scholarly articles to identify major authors, institutions, countries, and thematic groups. The findings of the research pinpoint a discernible chronological development—early research into pollution detection and environmental monitoring systems giving way to subsequent emphasis on financial tools such as green bonds, sustainable development investments, and decentralized finance. Keyword co-occurrence and overlay visualization show how environmentally pertinent data increasingly is being made part of financial decision-making and policy-making. In addition, the study reveals Chinese, American, Indian, and certain European country regional leadership in terming the story. Findings reveal theoretical and empirical contributions through the convergence of environmental science and financial innovation, as well as discovering limitations towards database scope and metrics by citation. Lastly, the study provides a strategic model for scholars, investors, and policymakers seeking to align environmental intelligence with sustainable finance practice.